Experimental Study of Cellulose Extraction From Oil Palm Empty Fruits Bunches - Zulnazri, Zulnazri; Adha, Muhammad Ikhwanul; Dewi, Rozanna (Jurnal IPTEK, 2022)
Empty Palm Oil Bunches is one of the non-timber solid wastes produced in the process of making palm oil. Empty palm oil bunches that have been cleaned and then hydrolyzed with HNO3 and NaNO2 are 3.5% at a temperature of 90oC. Then it was delignified by varying the concentration of NaOH 1%, 2%, 3%, 4% and using temperature variations of 40 oC, 50 oC, and 60 oC for 1 hour. Then the cellulose obtained was tested by FTIR test, XRD test, SEM test, and the yield was calculated. From the results of the FT-IR test, it is obtained that the high wave number is 2800-3300 cm-1 and the low wave number is 500-1400 cm-1. The spectrum shows a broad absorption peak located at 2800-4000 cm-1 which is a stretch of the –OH group. The highest yield content was found at a concentration of 4% NaOH at 90oC with a yield of 90.4%. The lowest yield is found at a concentration of 3% NaOH at a temperature of 60oC with a yield of 24.88%. From the results of these studies, it can be seen that the greater the concentration of NaOH used affects the cellulose produced.